Mercúrio em componentes bióticos e abióticos do Lago Grande de Manacapuru, Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
After the proven power of evil mercury (Hg) to human health, studies have focused on identifying the sources and pathways describe biogeochemical circulation in the environment. In Brazil, the use of Hg during the amalgamation of gold was considered the main source of contamination; however, today the contribution due to the deforestation and burning of forests has become relevant. In the Amazon, the dynamics of Hg in rivers (Negro, Madeira, Acre and Tapajós) is well known, but not in the floodplain, environments recognized as Hg methylation places and socioeconomic importance. To extend this knowledge we analyzed Hg levels in the biotic and abiotic components of Grate Lake Manacapuru (AM), the bioconcentration factor, the biomagnification potential to fish community, and bioaccumulation for commercial fish species were calculated. The Hg levels between 75.89 to 283.99 ng.g-1, being significantly higher in the flood and the podzolic soils. 64.3% of Hg levels measured in sediments were within the range of observed values to not contaminated Amazonian rivers (<200 ng.g-1), and 35.7% for highly anthropogenic rivers. The Hg levels water samples ranged from 1.7 to 15.2 ng.l-1. Emergent aquatic macrophytes and its fine particulate matter and periphyton presented high total Hg levels. Macroinvertebrate omnivores/detritivores and piscivorous fish associated with aquatic macrophytes recorded the highest Hg levels (226.4 ng.g-1 and 866.3 ng.g-1 respectively). There biomagnification in fish, the average Hg levels ranged from 45.89 to 527.82 ng.g-1, depending on the trophic category. The biomagnification factors were 0.27 for first order consumers, 0.33 for second order and 0.47 in thirth order. There were significant differences in the bioconcentration and total Hg level between the categories of third trophic level and the others. Plagioscion squamosissimus and Calophysus macropterus presentes Hg levels above those permitted by law (500 ng.g-1), and other six species also present risks to human health. The trophic structure of the community defined by the potential biomagnifications (b=0.15 ng.g-1) were 13 trophic categories, and five trophic levels. There were significant differences in total Hg levels of in relation to the trophic level of omnivores, detritivores, herbivores/frugivores, carnivores/ piscivores and carnivores/insectivores, and overlap in Hg levels of various categories, apparently resulting from the trophic plasticity of organisms and ontogenetic factors. In conclusion, the use of soil facilitates the release of Hg, which is carried by leaching into the aquatic environment where it is retained in the sediment. Sediment resuspension and homogenization of the water, facilitates the distribution and methylation of Hg in the lake, increasing the bioavailability to biota and their transfer into the food chain. The aquatic macrophytes and the periphyton community contribute to methylation, distribution and transfer of Hg in food chains. The processes of bioaccumulation in species are linked primarily to diet, but population factors such as age, growth, and fat levels should contribute to the different bioaccumulation factors observed.
Keywords: Bioacumulação; Biomagnificação; Bioconcentração; Áreas alagadas; Macrófitas aquáticas; Isótopos estáveis; Desmatamento; Antropização; Ecotoxicologia; Bioaccumulation Biomagnification; Bioconcentration; Floodplain; Aquatic macrophytes; Stables Isotopes; Deforestation; Anthropization; Ecotoxicology; RECURSOS PESQUEIROS E ENGENHARIA DE PESCA